Recycling of medicines: Environmental responsibility - Moreira Vieira, Karla; Lobo, Fabiana Aparecida; Louzada Miranda, Anderson; Azevedo, Calliana; Santos, Keisyanne; Silva, Lorena; Santos, Matheus; Almeida, Ricardo; Torres, Suzane; Cruz, Thayza; Cunha, Rafaela; Correa, Savio (Guará Journal, 2025)
This paper reports a matter of concern related to the preservation of the environment and public health: the indiscriminate disposal of medicines (remedies) household waste, surface water and landfills. These drugs are considered micro-organic contaminants that bring serious harm to human health and the environment. For lack of information the population ends up having attitudes that enhance further the various problems that this can cause indiscriminate disposal. Within this context, attitudes are proposed simple but of great benefit to the environment and public health: the recycling of drugs, the same correct destination and public awareness of this issue.
Keywords: Disposal of medicines; Health; Environment